Auditory frequency discrimination in children with dyslexia - Halliday, L; Bishop, D (2006)
A popular hypothesis holds that developmental dyslexia is caused by phonological processing problems and is therefore linked to difficulties in the analysis of spoken as well as written language. It has been suggested that these phonological deficits might be attributable to low-level problems in processing the temporal fine structure of auditory cues. Evidence for this has come from studies showing poor performance of dyslexic individuals on measures of auditory frequency discrimination (FD). We compared the FD thresholds of 28 children with dyslexia to 28 age-matched controls aged 6-13, on a task that minimised demands on short-term memory. To investigate the mechanisms involved in potential FD deficits, FD thresholds were measured at 1 kHz, where temporal cues were available, and at 6 kHz, where they were not. The dyslexic group had significantly higher FD thresholds than controls in both the 1- and 6-kHz conditions. These findings confirm that children with dyslexia often have poor FD, even when, as in this sample, they have normal language comprehension and expressive vocabulary, and when they are tested using a paradigm that minimises memory demands. However, their perceptual deficit was evident for both the 1- and 6-kHz tones, and so cannot readily be explained in terms of problems in processing temporal fine structure. © United Kingdom Literacy Association 2006.